2004
DOI: 10.1242/dev.01432
|View full text |Cite
|
Sign up to set email alerts
|

Caspase inhibition during apoptosis causes abnormal signalling and developmental aberrations inDrosophila

Abstract: Programmed cell death or apoptosis plays an important role in the development of multicellular organisms and can also be induced by various stress events. In the Drosophila wing imaginal disc there is little apoptosis in normal development but X-rays can induce high apoptotic levels,which eliminate a large fraction of the disc cells. Nevertheless, irradiated discs form adult patterns of normal size, indicating the existence of compensatory mechanisms. We have characterised the apoptotic response of the wing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
358
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(386 citation statements)
references
References 39 publications
14
358
1
Order By: Relevance
“…4,36,37 Although more clearly detected in 'undead cells', mitogen gene expression and extra proliferation have also been detected in genuine apoptotic cells. 4,36,38 It was proposed that the initiator caspase Dronc leads to Dp53 expression, which in turn activates mitogen gene expression, 7,34 but the specific roles of Dp53 and DDNp53 remain to be established. Here we showed that DDNp53 is a potent inducer of wg expression both in the 'undead cell' and genuine apoptotic cell models (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…4,36,37 Although more clearly detected in 'undead cells', mitogen gene expression and extra proliferation have also been detected in genuine apoptotic cells. 4,36,38 It was proposed that the initiator caspase Dronc leads to Dp53 expression, which in turn activates mitogen gene expression, 7,34 but the specific roles of Dp53 and DDNp53 remain to be established. Here we showed that DDNp53 is a potent inducer of wg expression both in the 'undead cell' and genuine apoptotic cell models (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation that apoptotic cells actually release themselves the signals that trigger proliferation of the surviving neighbouring cells came in 2004 with the possibility genetically to produce 'undead' cells in Drosophila wing discs -that is, cells where the caspase inhibitor p35 is overexpressed to allow the cells to start, but not to terminate, the apoptotic process [64][65][66] . In this context, the immortalized apoptotic cells indeed release signaling molecules after apoptosis induction, signals that trigger a proliferative response, although part of the effect might be linked to the undead status of these cells 67 .…”
Section: The Hydra Model Confirms the Link Between Apoptosis--inducedmentioning
confidence: 99%
“…[1][2][3][4] This suggested that apoptotic cells can release mitogenic signals to promote tissue repair and regeneration (Supplementary Figure S1B). Candidates for mitogens produced by apoptotic cells included the products of the signaling genes wingless (wg) and decapentaplegic (dpp), which are activated under these conditions.…”
mentioning
confidence: 97%
“…2,4,5 One important finding was that the secretion of Wg and Dpp is not limited to undead cells, but also occurs in 'genuine' apoptotic cells. 1,3,4,6 These observations suggested that the proliferation mediated by apoptotic cells might have an important role in CP, 1,3,4 as it would be instrumental in the restoration of normal size after massive cell death. However, flies carrying mutations in both wg and dpp are still capable of CP after high levels of X-rays induced apoptosis.…”
mentioning
confidence: 98%